Age Estimation from Ossification of the Medial Clavicular Epiphysis by Computed Tomography - El Morsi,Doaa A. (Sociedad Chilena de Anatomía, 2015)
The current study intended to evaluate the accuracy of age estimation from the development of the medial clavicular epiphysis (sternal end of the clavicle) in Egyptian population using computed tomography (CT) and to develop a discriminant formula that can be used in Egyptians. The study was conducted on 142 subjects (84 males and 58 females) after taken informed consent. They were subjected to multi-slice CT on the medial end of clavicles of both sides. The results revealed that the age of non - union was seen at 817 years; incomplete union at 1520 years and complete union was seen at 20 years. It is concluded that the ossification of medial clavicular end could be used for age estimation. Also CT is a good visualization tool to be used. Regression analysis for each and both clavicles in both sexes is specific to Egyptian population and should be used after validation of the results in other ones. The study recommended using stage 1 to be <17 years; stage 2 to be >15 years; Stage 3 to be >15 years; stage 4 of maturation to be >19 years and stage 5 to be >21 years.